Mothers and daughters in Arab women's literature the family frontier - Abudi, Dalya. (Women and Gender: The Middle East and the Islamic World, 2011)
This study explores the mother-daughter relationship as the most fundamental and most intimate female relationship and as the cornerstone of Arab family life. Drawing on autobiographical and semifictional works by women writers from across the Arab world, the study offers a first-hand account of how Arab women view and experience this primary bond. The author uses both early and contemporary writings of Arab women to illuminate the traditional and evolving nature of mother-daughter relationships in Arab families and how these family dynamics reflect and influence modern Arab life. The compelling narratives demystify the institutions of family and motherhood and show the potential of mothers and daughters to transform the patriarchal family and thus the fabric of Arab society. A groundbreaking work that fills a void in cross-cultural studies, it is of interest to scholars and students of Middle Eastern studies, women's studies, and family studies.